Personality Traits and Success in Foreign Language Acquisition - A I Krupnov; Yu V Kozhukhova (Peoples' Friendship University of Russia (RUDN University), 2012)
The article considers such personality traits as persistence, responsibility and sociability in the vein of the system-functional approach to the research of the personality and their impact on successful foreign language learning.